(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To identify the future scope in Energy resources using various Energy resources like Hydro, Wind, Thermal, Biomass and others using Classification methods like Bayesian Classification and EM algorithm. Forecasting of Energy demand is identified by using the previous year’s statistical data. Applying Time series forecasting methods which is implemented using WEKA. The best algorithm is identified by comparing the Evaluation parameters of various Time Series methods and the best method is used for predicting the future demand.